2019
DOI: 10.1021/acs.jpcc.8b12123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Liquid Structure on the Oxygen Reduction Reaction Under Humidified Conditions

Abstract: The oxygen reduction reaction (ORR) is widely studied in room-temperature ionic liquids (RTILs) but typically in dry environments. Because water is known to affect diffusion coefficients and reaction outcomes, the influence of water on the ORR is expected to be significant. We have therefore studied the effect of RTIL structure on the ORR at different relative humidity (RH) levels using cyclic voltammetry. A broad range of cations including imidazolium, ammonium, pyrrolidinium, pyridinium, sulfonium, and phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 67 publications
4
34
0
Order By: Relevance
“…The change in the mechanism results in much larger currents recorded in wet conditions compared to dry conditions. The ORR was studied in a wide range of ILs with different anions and cations, and the IL structure was found to have a very large influence on the ORR currents in humidified conditions . At high humidities, currents increased in ILs according to the trends associated with the bulk solubility of water (up to a 6 times current increase for an imidazolium IL with the hydrophilic [BF 4 ] − anion).…”
Section: Effect Of the Edl On Electrochemical Applications Of Ionic L...mentioning
confidence: 78%
See 3 more Smart Citations
“…The change in the mechanism results in much larger currents recorded in wet conditions compared to dry conditions. The ORR was studied in a wide range of ILs with different anions and cations, and the IL structure was found to have a very large influence on the ORR currents in humidified conditions . At high humidities, currents increased in ILs according to the trends associated with the bulk solubility of water (up to a 6 times current increase for an imidazolium IL with the hydrophilic [BF 4 ] − anion).…”
Section: Effect Of the Edl On Electrochemical Applications Of Ionic L...mentioning
confidence: 78%
“…By keeping the IL anion constant ([TFSI] − ) and changing the cation, it was shown that more hydrophilic cations (e.g., in [C 2 mim] + or [C 4 mpyrr] + ) in the EDL can be easily penetrated by water, which can then react with the electrogenerated superoxide radical. However, for much more hydrophobic cations (e.g., [P 6,6,6,14 ] + ), the dense hydrophobic layer formed at the electrode (due to the presence of long alkyl chains) effectively prevents water molecules from reacting with the electrogenerated superoxide radical in the interfacial region (see Figure a) . This was confirmed by AFM studies that showed that the [C 2 mim] + interfacial structure was obvious in dry conditions (see Figure b) but collapsed at 40% relative humidity .…”
Section: Effect Of the Edl On Electrochemical Applications Of Ionic L...mentioning
confidence: 93%
See 2 more Smart Citations
“…Voltammograms recorded at both unmodified and modified SPCE-RTILs showed a single cathodic peak located at about −0.85 V to which a very small return peak was associated in the reverse scan. This behavior, similar to that previously reported for the O 2 reduction in other RTILs, , pointed out that the prevailing reduction pathway is that usually occurring in wet media. On the other hand, Karl Fisher titrations conducted on the [BMIM]­[NTF 2 ] employed by us indicated the presence of a water content of about 0.23% w/w.…”
Section: Resultsmentioning
confidence: 99%